Konsep Keuntungan dalam Syirkah Al-Inan dari Perspektif Ekonomi Islam - Musliadi (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2021)
The dissertation is about the study on the concept “profit in syirkah al-inan from the Islam Economic System Perspective.” In order to achieve the aboveobjectives the Writer has adopted the following methodology in his study:Gathering data/information from a number of libraries and institutions; Field study by studying data from Bank Rakyat to enhance the information needed. In addition the Writer uses the interview method.The interview method was used to conduct interview with the respondent who are directly involved with the topic of the study example the Manager and the Syariah executive in the aforesaid bank; andRelied on the Quran, Hadiths the opinion of the Ulamas whose opinion have been deeply engraved in the famous books and the study made by the current Islamic thinkers.Based on this study, the Writer was able to comprehend the concept of profit in syirkah al-Inanfrom the Islam economic perspective. The Writer found out, musyarakah orsyirkah is a form of cooperation between two people or more to undertake a business or activity which is motivated by profit.